Analisis Kemampuan Berpikir Reflektif Dalam Menyelesaikan Soal Cerita Matematika Ditinjau Dari Gaya Belajar Pada Siswa SMA - Nisa, Khaerun; Akib, Irwan; Nasrun (Wacana Akademika: Majalah Ilmiah Kependidikan, 2023)
This study aims to analyze the ability to think reflectively in solving math word problems in class XI SMA Muhammadiyah Sungguminasa. This type of research is descriptive research with a qualitative approach. The instruments used were a learning style questionnaire, a reflective thinking ability test and an interview guide. The subjects in this study were 3 students of class XI SMA Muhammadiyah Sungguminasa, each of which represented a category of visual learning styles, auditory learning styles and kinesthetic learning styles. The data collection technique used is to provide learning styles, reflective thinking ability tests and interviews. Data analysis techniques in this study are data condensation, data presentation and data verification. The results showed that students with visual and auditory learning styles were able to fulfill 4 indicators of reflective thinking skills. So that this subject includes students who have good reflective thinking skills. Meanwhile, students with a kinesthetic learning style are only able to fulfill 2 of the 4 indicators of reflective thinking skills.